Ability of prostate specific antigen to predict bone scan result in prostate cancer patients (Medical Journal of Indonesia, 2004)
The objective of this study is to assess the relation between serum prostate specific antigen (PSA), clinical tumor stage, tumor grade, and bone scan result in an attempt to seek the ability of serum PSA to predict bone metastases in newly diagnosed prostate cancer patients. A retrospective analysis was conducted on clinical files of prostate cancer patients which were diagnosed in our institutions between January 1995 and December 2003. Patients on which initial serum PSA were obtained after urethral manipulation or after receiving therapy were excluded. The results of bone scans were related to levels of serum PSA, clinical tumor stage, and tumor grade. Of 103 patients who were included in this investigation, 61 patients (59.2%) had a positive bone scan and 42 patients (40.8%) had a negative bone scan with mean PSA value 471.13 ± 853.34 ng/ml and 61.00 ± 124.47 ng/ml respectively (p < 0.05). The risk of having a positive bone scan increased with advancing serum PSA levels, clinical tumor stage, and tumor grade (p < 0.05). Using receiver operating characteristic curves, PSA had the best correlation with bone scan results (the area under curve was 0.812). Bone scan results were predicted best by the combination of serum PSA, clinical tumor stage, and tumor grade. Bone scans were positive in 5 of 19 patients with PSA level < 10 ng/ml. None of 8 patients with PSA levels < 10 ng/ml, clinical tumor stage T1 or 2 and tumor grade 1 or 2 had a positive bone scan. In conclusion, we suggest that routine bone scan examination may not be necessary in patients with newly diagnosed, untreated prostate cancer, who have serum PSA level < 10 ng/ml with clinical tumor stage T1 or 2 and tumor grade 1 or 2. (Med J Indones 2004; 13: 151-5)Keywords: prostate cancer, bone metastases, tumor grade, tumor stage